Emarginazione e integrazione sociale: considerazioni cliniche - Tommaso Fratini (Firenze University Press, 2012)
Drawing on the psychoanalytic theory of object-relations, in particular according to the post-Kleinian model, the foundation of social integration is taken in relation to the ability to share authentic relationships with others, alongside the individual task of building a sufficient integration of personality. The marginalization is attributed instead to a failure in the ability to share, which is associated with schizoid withdrawal and operated processes of social exclusion by the social community and by the affiliated group.